The Role of Signalling Pathways in Myocardial Fibrosis in Hypertrophic Cardiomyopathy - Patryk Skórka; Jakub Piotrowski; Estera Bakinowska; Kajetan Kiełbowski; Andrzej Pawlik (Reviews in Cardiovascular Medicine)
Hypertrophic cardiomyopathy (HCM) is the most prevalent hereditary cardiovascular disorder, characterised by left ventricular hypertrophy and cardiac fibrosis. Cardiac fibroblasts, transformed into myofibroblasts, play a crucial role in the development of fibrosis. However, interactions between fibroblasts, cardiomyocytes, and immune cells are considered major mechanisms driving fibrosis progression. While the disease has a strong genetic background, its pathogenetic mechanisms remain complex and not fully understood. Several signalling pathways are implicated in fibrosis development. Among these, transforming growth factor-beta and angiotensin II are frequently studied in the context of cardiac fibrosis. In this review, we summarise the most current evidence on the involvement of signalling pathways in the pathogenesis of HCM. Additionally, we discuss the potential role of monitoring pro-fibrotic molecules in predicting clinical outcomes in patients with HCM.